β-Hemoglobinopathies lead the way - Saunthararajah, Yogen (Blood, 2021)
In this issue of Blood, guided by clinical observations and needs, Gong et al have identified a germline missense mutation in DNA methyltransferase 1 (DNMT1), a ubiquitously expressed key epigenetic regulator, as a cause of hereditary persistence of fetal hemoglobin (HPFH). HPFH protects against β-thalassemia and sickle cell disease (the β-hemoglobinopathies).(1) Discussed here is how these findings by Gong et al continue the pioneering role of the β-hemoglobinopathies as a model of discovery for all biomedicine. Sickle cell disease, after all, is the “first molecular disease”: altered migration of sickle vs normal hemoglobin in gel electrophoresis demonstrated, for the first time, that the structure–chemical basis for disease is discoverable and knowable.(2)